Effects of self-congruity, satisfaction, and trust on value co-creation behaviour and loyalty of cooperative members’ / Yusman Yacob - Yacob, Yusman (2019)
Value co-creation has received enormous attention by researchers over the past decades. Evidently, past research reveals that value co-creation is pivotal to the growth and survival of the service industry. While most recent studies focus on conceptualising value co-creation dimensions and its antecedents, there is a lack of study which looks into its impact in relation to behavioural factors. Applying Service Dominant (S-D) Logic theory supported by Social Exchange and Self-Image Congruence theories, this research attempts to examine the value co-creation behaviour (member participation and member citizenship behaviours) and its effect on members’ loyalty towards credit cooperatives in Sarawak. Although past studies have investigated the relationship between value co-creation behaviour and loyalty, little is done to determine the effect of satisfaction and trust as mediators and self-congruity as a moderator, which are found important in the service sectors. Additionally, how the aforementioned is implied in the context of cooperatives in developing markets still remains unknown. Utilising a quantitative approach by means of purposive sampling technique, 395 valid cooperatives’ members were sampled throughout Sarawak. Self-administered questionnaire was distributed and collected by hand and the data were keyed in and screened. Partial Least Squares Structural Equation Modelling (PLS-SEM) technique was then used to test the hypothesized relationships as well as the mediation and moderation effect.